Kemampuan Numerasi Siswa Kelas VIII Materi Teorema Pythagoras melalui Pendekatan RME Konteks Origami - Haniefa Indira Janita; Novita Sari (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
Motivated by the low numeracy skills of students, this study aims to describe the numeracy skills of eighth-grade students in the Pythagorean Theorem material through the Realistic Mathematics Education (RME) approach with an origami context. A total of 30 eighth-grade students from a public junior high school in Prabumulih, South Sumatra, were the subjects of this study. The research method used was descriptive with data collection through tests and interviews. The stages in this study included preparation, implementation, and data analysis. The data were analysed qualitatively based on numeracy ability indicators: (1) using various numbers and symbols related to basic mathematics to solve problems in various contexts of daily life; (2) analysing information presented in various forms (graphs, tables, diagrams, etc.); and (3) using the interpretation of the analysis results to predict and make decisions. The research findings show that the numeracy skills of Grade VIII students are in the moderate category, with an average of 79.17. The most frequently appearing numeracy skill indicator is the first indicator, while the third indicator has the lowest frequency of appearance.